Local Policy Implementation on Early Marriage Education Among High School Students In Ternate City - Nuraini Umasugi; Muhlis Hafel; Tita Rosita (CV. Tripe Konsultan, 2026)
Early marriage remains a significant social issue in Ternate, Indonesia, as indicated by data from several relevant institutions showing consistently high rates. This condition prompted the local government to issue Mayor Regulation (Perwali) No. 2 of 2021 concerning the prevention of early marriage. This study aims to analyze the implementation of this policy, particularly among senior high school students in Ternate City. A qualitative research approach was employed, utilizing data collection techniques such as observation, in-depth interviews, and documentation review. The study involved four key informants and was complemented by questionnaire data from 100 senior high school students. The findings reveal that the implementation of the mayoral regulation has not been carried out optimally. Limited dissemination and lack of effective communication strategies have resulted in low levels of awareness among students regarding the existence and objectives of the policy. The questionnaire results further confirm that most students are unfamiliar with Mayor Regulation No. 2 of 2021, indicating weak policy outreach and engagement. This study highlights the need for more comprehensive policy implementation strategies, particularly through educational institutions and community-based approaches, to enhance awareness and effectiveness. Strengthening coordination among stakeholders and improving policy communication are essential to achieving the intended outcomes of early marriage prevention.